Nâng cao hiệu quả suy diễn tự động trong bài toán chứng minh - Thủy, Nguyễn Thanh; Đức, Nguyễn Hữu; Hưng, Nguyễn Vũ Quốc (Journal of Computer Science and Cybernetics, 2016)
In this paper we shall investigate some  techniques and strategies for  improving the inference efficiency in automatic proof. We  propose three types of techniques. Restriction and filtering,  heuristics – based technique and learning. The two typical knowledge representations ( propositional logics and  predicate logics) and corresponding proposed heuristics are carefully considered. We applied already these techniques in an Intelligent Tutoring System for  geometrical proof problem Geometry.